Developing a fuel cell industry in South Africa: a triple-helix analysis - Peverelle, Franca (My University, 2018)
Globally, the concept "knowledge economy" has evolved as the dominant economic logic that is premised on the importance of new knowledge for innovation and competitiveness, and on the sharing of that knowledge through various forms of knowledge transfer based on collaboration. This is the context of this study, which focuses on how knowledge transfer and the relationship between university, industry and government impact the development of the fuel cell industry in South Africa as informed by the triplehelix systems theory. From the literature it is evident that the beneficiation potential of South Africa is a top development priority for policymakers with a view to boosting the country’s economic potential. Furthermore, South Africa is reportedly not leveraging its natural platinum resources effectively, resulting in high levels of raw-platinum exportation and high levels of platinum product imports. The problem statement thus suggests that supporting and developing a local fuel cell industry in South Africa through active partnerships between universities, industry and government may contribute to a reduction in the amount of raw platinum being exported, exploiting the platinum reserves for heightened South African economic development. This is a qualitative case study comprising semi-structured interviews based on the selection of participants through purposive and snowball sampling techniques. The Hydrogen South Africa programme, a large player in the South African fuel cell industry, has partnered with three South African universities, namely North-West University, University of Cape Town and Western Cape University, to develop various elements of hydrogen fuel cells, providing a key opportunity for a case study on the current relationship between university, industry and government in the fuel cell industry. The triple-helix system depicts the importance of the roles played by universities, industry and government as well as the importance of collaboration among them. Overall, this study aims to demonstrate the potential power of the triple-helix system to allow for the development of a globally competitive local fuel cell industry that may reduce the exportation of platinum resources for beneficiation purposes, rather utilising the potential within South Africa. This study will firstly explore the role of higher education institutions in supporting the development of the required skills for the fuel cell industry through relevant research and development projects that may result in fuel cell technology innovations and commercialisation opportunities. Secondly, the study will seek to demonstrate industry's role in continuously advancing workers’ skills through training and active knowledge transfer in collaboration with universities, as well as b eing involved with research and development projects at universities and research institutes with the aim of developing the fuel cell industry. The study will thirdly seek to document government’s role in providing support and guidance in the form of policy development and funding for research initiatives in the science and technology innovation space, as well as its role as mediator between the education and industrial sectors.
A thesis submitted in accordance with the requirements for the degree Master of Education (M. Ed.) from the University of the Witwatersrand, May 2018
Keywords: Knowledge management; Academic-industrial collaboration; Intellectual capital